Electrostatic Stabilized InP Colloidal Quantum Dots with High Photoluminescence Efficiency - Mnoyan, Anush N.; Kirakosyan, Artavazd Gh.; Kim, Hyunki; Jang, Ho Seong; Jeon, Duk Young (AMER CHEMICAL SOC, 2015)
Electrostatically stabilized InP quantum. dots (QDs) showing a high luminescence yield of 16% without any long alkyl chain coordinating ligands on their surface are demonstrated: This is achieved by UV-etching the QDs in the presence of fluoric and sulfuric acids. Fluoric acid plays a critical role in selectively etching nonradiative sites during the ligand-exchange process and in relieving the acidity of the solution to prevent destruction of the QDs. Given that the InP QDs show high luminescence without any electrical barriers, such as long alkyl ligands or inorganic shells, this method can be applied for QD treatment for application to highly efficient QD-based optoelectronic devices.
Keywords: NANOCRYSTALS